1979
DOI: 10.1002/pol.1979.180170504
|View full text |Cite
|
Sign up to set email alerts
|

Rheo‐optical studies on the deformation mechanism of semicrystalline polymers. IV. On the nature of alpha mechanical dispersion of low density polyethylene in relation to the mechanism of spherulite deformation

Abstract: The dynamic mechanical and birefringence behavior of three kinds of test specimens, prepared from a low‐density polyethylene by different heat treatments, was investigated over the frequency range 0.008 to 4.3 Hz at various temperatures from 20 to 80°C. Reduction of both kinds of data to the common reference temperature of 50°C revealed rather broad frequency dispersions, corresponding to the α dispersion, with activation energies for the mechanical and optical relaxation processes of around 25 kcal/mole for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
2
1

Year Published

1980
1980
2004
2004

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 58 publications
0
13
2
1
Order By: Relevance
“…In contrast to the strain-orientation coefficient function Ct, 22 to be positive or negative. Although the master curves are again the 'apparent' ones in the sense that the system has different orientation-retardation mechanisms, as suggested above, the following anomalies in the dynamic-orientation behavior must be noted: Die and Die' becoming opposite in sign as observed for Dt and Di at relatively high reduced frequencies, for Di at moderate frequencies, and for Dt at low frequencies; D~ and D; exhibiting a distinctive positive maximum and a slight negative minimum, respectively, at moderate frequencies, not of leveling off but of a change in sign with further decreasing frequency.…”
Section: Dynamic Crystal Responsesmentioning
confidence: 88%
See 1 more Smart Citation
“…In contrast to the strain-orientation coefficient function Ct, 22 to be positive or negative. Although the master curves are again the 'apparent' ones in the sense that the system has different orientation-retardation mechanisms, as suggested above, the following anomalies in the dynamic-orientation behavior must be noted: Die and Die' becoming opposite in sign as observed for Dt and Di at relatively high reduced frequencies, for Di at moderate frequencies, and for Dt at low frequencies; D~ and D; exhibiting a distinctive positive maximum and a slight negative minimum, respectively, at moderate frequencies, not of leveling off but of a change in sign with further decreasing frequency.…”
Section: Dynamic Crystal Responsesmentioning
confidence: 88%
“…The dynamic crystal-orientation behavior of this bulk-crystallized high-density polyethylene is significantly different from that of a low-density polyethylene. 22 For the high-density polyethylene, the behavior at low reduced frequencies corresponding to the CJ. dispersion region is dominated in terms of the rotation of the crystal grains around the crystal b-axis in association with the lamellar detwisting mostly concentrated at the equatorial zone of spherulites.…”
Section: Dynamic Crystal Responsesmentioning
confidence: 99%
“…Sci., Polym. (44) Hashimoto, T.; Shibayama, M.;Kawai, H.;Watanabe, H.;Kotaka, T. Macromolecules 1983, 16, 361. Ed.…”
mentioning
confidence: 99%
“…In the case of that polymer it has been shown that the spherulite size distribution and perfection of the spherulite structure strongly affect the nature of the relaxation process [1,2,4,11,12]. In the semicrystalline polymers, such a process is often characterized by the two components denoted by al and a2.…”
Section: Introductionmentioning
confidence: 97%